Une cachette d’objets de valeur des années 260 apr. J.-C. dans une villa de la cité des Nerviens (Merbes-le-Château, Belgique) - Nicolas Paridaens; Nicolas Authom; Sébastien Clerbois; Marie-Paule Delplancke; Johan van Heesch (Gallia)
The Gallo-Roman villa at Champ de Saint-Éloi in Merbes-le-Château (Belgium) lies by the river Sambre, at the eastern limit of the civitas Nerviorum. During the 2nd and 3rd centuries it was constituted of an imposing dwelling with adjacent buildings for economic functions and ornamental structures. A hoard of precious items was recovered inside the main building, in a small semi-buried room. It consists of two copper-allied caldrons and of a small casket containing two silver spoons, a purse with 122 silver antoniniani, a glass flask and four worn sestertii deposited on a plaque dedicated to the Danubian Riders. This copper-allied tinned plaque is remarkable for its rarity in the western provinces as for the high technical degree quality of its decoration. The originality of the hoard, buried in the 260s AD, comes from its heterogeneous contents: daily and precious items and a religious object are mixed.